Lexical and cultural meaning Mitoni tradition of Javanese society in Plumbungan Village, Banyudono, Boyolali: An ethnolinguistic studies - Rosidah, Khotimatul; Lutfiana, Aufa Daffa; Lestari, Clarisma Avistha; Nugroho, Miftah (Universitas Dian Nuswantoro, 2024)
Mitoni is one of the seven monthly traditions of pregnant women carried out by the Javanese community; each series of events and ubarampe has its meaning for the community. This study aims to describe the lexical and cultural meanings of the series of events and ubarampe in the mitoni tradition in Boyolali Regency. This research is ethnolinguistic in nature because it explains the relationship between language and culture in Plumbungan Village, Banyudono District, Boyolali Regency. This research is a qualitative descriptive study. Data collection methods used participatory observation followed by recording techniques and note-taking techniques. Methods of data analysis using the equivalent method. The results of this study indicate that the lexicon in the mitoni tradition is (1) sesajen, (2) siraman, (3) mecah tigan, (4) brojolan, (5) solan salin, and (6) kondangan. While the ubarampe found were (1) kembang, (2) banyu pitung sumur, (3) jimbeng, (4) gedhang raja, (5) kinang, (6) takir pontang, (7) duit koin, (8) jarik lumpatan, (9) cengkir, (10) jenang procot, (11) tumpeng, (12) gudhangan, (13) rujak, (14) tigan jawa, and (15) jenang cenil. Each of these lexicons has a symbol of life for the Banyudono people.